(untitled) (Scientific journal of the Fergana State University, 2025)
This article examines certain terms and words related to the vocabulary of jewelry and decorative arts based on the first volume of “Shahname” by Abulkosim Firdavsi. The researcher has concluded that, in addition to depicting ancient history, Firdavsi was well aware of the customs of adornment, the art of jewelry-making, and the names of objects associated with the vocabulary of jewelry and decoration. Moreover, he provided historical and artistic information about the discovery of these materials. Firdаvsi’s poetic mastery and unique style are evident in how he skillfully weaves all these elements into verse, like threading precious gems. As a result, his work has been preserved through the ages, enriching the lexical composition and terminology related to jewelry and decorative arts.